Between the Cherubim The ‘Mercy Seat’ as Site of Divine Revelation in Romans 3.25 - Porter, Nathan (2021)
Although the long-standing debate about the meaning of hilastērion in Rom. 3.25 has led to no consensus, readings are nearly always either (1) metaphorical (hilastērion as place of atonement/expiation) or (2) metonymic (hilastērion as a means of atonement/expiation). However, in many Second Temple Jewish texts, the word refers to a place of divine revelation. Proposing a fresh semantic topology of usages of hilastērion, this article argues that there is no unambiguous metonymic usage of the word, and that references to atonement in Lev. 16 are secondary to the revelatory function of the ‘mercy seat’. Attending to overlooked intertextual complexities, it suggests that the hilastērion was the site where God promised to reveal the definitive interpretation of his law. The revelatory function of the hilastērion possesses prima facie plausibility as a reading of Rom. 3.21-26, which is driven by the theme of God’s self-revelation in Jesus.